Externality and framing effects in a bribery experiment - Barr, A; Serra, D (2007)
Using a simple one-shot bribery game, we find evidence of a negative externality effect and a framing effect. When the losses suffered by third parties due to a bribe being offered and accepted are increased bribes are less likely to be offered and accepted. And when the game is presented as a bribery scenario instead of in abstract terms bribes are less likely to be offered and accepted. We discuss two possible reasons as to why our experiment leads to the identification of these effects while previous experiments did not.